Celiac Disease and Secondary Amyloidosis: A Possible Causal Association?. Issue 1 (2018) - Chhoda, Ankit; Jain, Deepanshu; Daga, Mradul Kumar; Batra, Vineeta
ABSTRACT : N/A: We report a rare case of secondary renal amyloidosis in a patient with probable celiac disease presenting as nephrotic syndrome. A 30‐year‐old man with chronic diarrhea presented with progressive anasarca for 2 years. On further evaluation, he had hypoalbuminemia, significant nephrotic‐range proteinuria, and elevated levels of anti‐tissue transglutaminase. Renal biopsy suggested deposition of amorphous Congo red‐positive material in the glomerular mesangium, positive for amyloid A amyloidosis. Endoscopic duodenal biopsy suggested blunting of the villous architecture and chronic inflammation of the lamina propria. The patient subsequently developed massive pulmonary embolism and died due to refractory cardiogenic shock.